Experimental electrical impedance tomography (EIT) - Chua, Yong Siang (2019)
Electrical Impedance Tomography (EIT) is a type of imaging technique where the impedance, permittivity, and electrical conductivity of a part of an object is taken from surface electrode measurements and used to form a tomographic image. This project focuses on crack detection in a tank, where electrodes are placed around the tank to monitor and detect if there is a crack inside the tank. There are a few problems in this system. One problem is that when the material used is too conductive, the voltage level obtained will be very low, therefore the differential values between homogeneous and inhomogeneous will be too insignificant to produce the tomographic image. Another problem is the system’s ability to detect faults, especially minor ones. For example, if a crack in the tank is very thin, or very far from the electrodes, the electrodes might not be sensitive enough to detect it. Therefore, the aim of this study is to improve upon the existing EIT technology in terms of its ability to generate the correct image and to detect minor faults. To achieve this, several experiments will be done with several different variables such as using materials of different conductivity, crack designs of different shapes and sizes, or changing the position of electrodes. Additional circuits such as op-amp and band pass filter circuits are implemented into the system to amplify the signal and eliminate noise.